Delayed Supra Choroidal Haemorrahge after Secondry Anterior Chamber Intra Ocular Lens Implant in a Patient on Warfarin Therapy - Tariq M Arian, Rao M Rashad Qamar, Muhammad a Ahad; Tariq M Arian, Rao M Rashad Qamar, Muhammad a Ahad (Pakistan Journal of Ophthalmology, 2007)
Purpose: To report a case of delayed suprachoroidal haemorrhage after secondary anterior chamber intra-ocular lens implant in a patient on anticoagulant therapy. Material and Method: An 80 years old patient, who had been on warfarin for 3 years underwent secondary anterior chamber implant through clear corneal incision under local anesthesia. The warfarin was stopped four days before the surgery and her International normalized ratio (INR) on the day of surgery was 2.7. Two weeks later, she developed suprachoroidal haemorrhage. Results: The suprachoroidal haemorrhage was managed conservatively and the condition settled down in one-month time. Conclusion: Serious sight threatening complications can develop in patients on anticoagulants even with minimal surgery.